Survival outcomes according to the tumor location and prognostic factor in metastatic rectal cancer: a multicenter retrospective cohort study - Unal, Olcun Umit; Akay, Seval; Semiz, Huseyin Salih; Keser, Murat; Demir, Gonul; Capar, Zeliha Guzeloz; Demirciler, Erkut; Yavuzsen, Tugba; Degirmencioglu, Serkan; Demir, Bilgin; Oktay, Esin; Gulmez, Meltem Demirtas; et al. (Frontiers in Oncology, 2024)
Background & Aims: Prognostic factors of metastatic rectal cancer are not well known. We aim to determine prognostic factors affecting survival for metastatic rectal cancer patients and also to investigate the effect of tumor localization on overall survival.Methods: Metastatic rectal cancer patients who received treatment in 5 different centers between 2012 and 2022 were included. Prognostic factors for survival were evaluated using univariate and multivariate analysis. The statistical methods included Pearson's chi-square test, Fisher exact test, Log-rank test, and Cox regression model.Results: A total of 283 patients with metastatic rectal cancer were included in the study. The median OS was not significantly different among the three groups (upper rectum 30.1 months, middle rectum 28.3 months, and low rectum cancer 24.8 months; log-rank p = 0.25). In univariate analysis, Grade 3, ECOG performance status 2, the presence of multiple metastatic sites, the presence of KRAS mutation, the presence of liver metastases, the presence of nonregional lymph node metastases, and the presence of bone metastases were significant predictors of poor survival. In multivariate analysis, Grade 3, ECOG performance status 2, and the presence of multiple metastatic sites were determined as indicators of worse prognosis. Conclusion: Our findings, primary tumor location did not affect survival in metastatic rectal cancer. The most important factors affecting survival were multiple metastatic sites, tumor grade, and ECOG performance status.